The Effect of Disease and Harvest in the Eco-Epidemical Food Chain Model - Yaseen, Rasha Majeed (Al-Nahrain Journal of Science, 2018)
This paper describes a three species food web model with linear functional response and incidence disease. This model consisting of a prey, intermediate predator and top predator where harvesting of top predator species and SIS disease spread in prey are taken into consideration. The stability analysis of all possible equilibrium points are carried out. We discussed the effect both of harvest and disease on the stability of this model. Finally, we used the numerical simulations to verify the analytical results.